Detroit Area Study, 2002 - Mohai, Paul ([Verlag nicht ermittelbar], 2009)
The 2002 Detroit Area Study (DAS) is a face-to-face survey of adults in the Detroit, Michigan tri-county area. Respondents were asked questions about their place of residence, level of political participation, general political attitudes, concern about the environment, environmental consumerism, environmental justice, and the quality of the environment in their current neighborhood and the neighborhood in which they were raised. Information was also collected on respondents' job responsibilities, current financial situation, the availability of childcare and transportation, and their own feelings of self-worth. Interviewer observations about the condition of the respondent's neighborhood were also included. Demographic variables include sex, age, race, ethnicity, marital status, household income, education level, employment status, occupation, and industry, labor union membership, religious preference, frequency of religious attendance, and the presence of children in the household.